The big five personality traits and its relationship with students' academic performance / Adibah Hussin, Mas'udah Asmui and Suhanom Mohd Zaki - Hussin, Adibah; Asmui, Mas'udah; Mohd Zaki, Suhanom (2015)
Students have unique and authentic personalities that differentiate one from another. The differences form and influence their academic performance. According to past researches, students' personality and academic performance are significantly interrelated. The past researches have mentioned the relationships between numerous variables including personality and academic performance among students. This paper identified the relationship between Big Five Personality Traits and academic performance among UiTM Pahang students specifically. The data was collected using a self-administered questionnaire and analyzed using SPSS version 22.0 statistical software. The result showed that there was no significant relationship between the Big Five Personality Traits and academic performance. However, it was found that conscientiousness was the strongest and neuroticism was the weakest trait possessed by UiTM Pahang students. Moreover, there was no difference between personality traits and genders yet there was difference between genders and academic performance.